2017
DOI: 10.1021/acschembio.7b00797
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Interactions of Mycobacteria with the Host Innate Immune System from a Novel Array of Synthetic Mycobacterial Glycans

Abstract: An array of homogeneous glycans representing all the major carbohydrate structures present in the cell wall of the human pathogen Mycobacterium tuberculosis and other mycobacteria has been probed with a panel of glycan-binding receptors expressed on cells of the mammalian innate immune system. The results provide an overview of interactions between mycobacterial glycans and receptors that mediate uptake and survival in macrophages, dendritic cells, and sinusoidal endothelial cells. A subset of the wide variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 66 publications
(128 reference statements)
6
81
1
Order By: Relevance
“…Overall, the direct interaction of PGL with host cell receptors is still unclear. Studies focused in determining which host receptors could recognize and bind M. tuberculosis complex BSA-conjugated glycans indicate that dendritic cellspecific ICAM-3-grabbing non-integrin (DC-SIGN or CD209), the DC-SIGN homolog DC-SIGNR (for DC-SIGN related), Langerin (CD207, C-type lectin receptor on Langerhans cells), the mannose receptor (MR or CD206), galactose receptor, dendritic cell C-type lectin 2 (Dectin-2), macrophage-inducible Ca 2+ -dependent lectin receptor (Mincle or CLEC4E), and BDCA-2 (CLEC4C or CD303) had low affinity for the rhamnose (6-deoxy-L-mannose) and fucose (6-deoxy-L-galactose) found in PGLs, indicating that PGL could be targeted by other, yet to be discovered, host C-type lectins (147).…”
Section: The Pgl Familymentioning
confidence: 99%
“…Overall, the direct interaction of PGL with host cell receptors is still unclear. Studies focused in determining which host receptors could recognize and bind M. tuberculosis complex BSA-conjugated glycans indicate that dendritic cellspecific ICAM-3-grabbing non-integrin (DC-SIGN or CD209), the DC-SIGN homolog DC-SIGNR (for DC-SIGN related), Langerin (CD207, C-type lectin receptor on Langerhans cells), the mannose receptor (MR or CD206), galactose receptor, dendritic cell C-type lectin 2 (Dectin-2), macrophage-inducible Ca 2+ -dependent lectin receptor (Mincle or CLEC4E), and BDCA-2 (CLEC4C or CD303) had low affinity for the rhamnose (6-deoxy-L-mannose) and fucose (6-deoxy-L-galactose) found in PGLs, indicating that PGL could be targeted by other, yet to be discovered, host C-type lectins (147).…”
Section: The Pgl Familymentioning
confidence: 99%
“…Interestingly, a different study revealed binding to array-printed mycobacterial phosphatidylinositol mono-and di-mannosides of the human soluble lectin ZG16p (Hanashima et al, 2015), putting forward a possible involvement of this lectin in the gastrointestinal immune system. The mannose receptor, present on macrophages and sinusoidal endothelial cells, was found to recognize several LAM cap and core structures (Zheng R. B. et al, 2017). However, its binding pattern clearly differed from that of DC-SIGN, as the presence of terminal Man residues was a main factor for recognition.…”
Section: Bacterial Glycan Arrays For Identification Of Ligands For Lementioning
confidence: 99%
“…In addition to AM and LAM, they comprise phosphatidyl-myoinositol mannosides, phenolic glycolipids, glycopeptidolipids, trehalose mycolates, trehalose-containing LOSs, and capsular α-glucans (Figure 1, right part). An array containing 60 chemically synthesized glycans, representing all these classes of mycobacterial structures, was screened with a panel of seven human C-type lectins as well as with bovine mincle (Zheng R. B. et al, 2017), all of them found on the surface of macrophages and/or dendritic cells. No ligands were identified for the macrophage galactose receptor, consistent with its specificity for GalNAc, which was absent from the array.…”
Section: Bacterial Glycan Arrays For Identification Of Ligands For Lementioning
confidence: 99%
See 1 more Smart Citation
“…However, covering the huge diversity of microbial glycans, oen containing rare sugars, remains a major challenge. 27 Efforts to access such glycans in a well-dened manner are still needed.…”
Section: Access To Glycan Collectionsmentioning
confidence: 99%